Disparitas Pendayagunaan Tanah Terlantar di Indonesia - I Made Pria Dharsana; I Gusti Agung Ayu Gita Pritayanti Dinar; Putu Lingga Dhananjaya; N. Nurnaningsih (Jurnal Preferensi Hukum, 2024)
The lack of optimal utilization of abandoned land in Indonesia is one of the elements of the problem that is quite worrying, in general, the legal consequences of abandonment of land are the termination of the legal relationship between the subject of the holder of land rights and the object of the land is given to the authorized official, while Article 9 paragraph (2) of government regulation no. 11 of 2020, in the case of land as referred to in Article 6 paragraph (1) letter a, the stipulation of abandoned as well as the stipulation of the abolition of land rights, as well as severing legal relations whose land is expressly controlled by state, research on legal issue in this paper uses the normative legal research method, which examine legislation, doctrine, principles. furthermore, regarding abandonment of land, its has legal consequences, one of which is eliminating the economic potential of land and it is unfair and also a violation of the obligation that must be carried out on rights holders who have land control, while utilization of state land in the field of regulatory provision and their implementation still erodes the function of the land so that the benefits are not felt by the community in terms of economic, social and political